Ineffective Feeding Practices and Their Effect on Malocclusion: A Narrative Review - Mokashi, Pratima R.; Bhandary, Srikala (Journal of Health and Allied Sciences NU, 2021)
Objective The aim of this narrative review is to highlight the association of ineffective feeding practices with the development of malocclusion in children and the role of a pediatric dentist in identifying the cues and signs of improper feeds, and encourage effective breastfeeding practices.Introduction There has been an ongoing debate on the role of effective breastfeeding in the prevention of malocclusion. Although no specific claim supports the positive impact of the same, a detailed reviewing of the literature helps to identify the method of feeding to be chosen considering health benefits and personal preference.Materials and Methods A broad search of all resources linked to the topic was performed in PubMed, Medline, World Health Organization web site, government web sites, and Google Scholar search engine. Keywords used in the search included breastfeeding, ineffective breastfeeding, bottle feeding, pacifier, and malocclusion. A total of 60 articles published in the period from 2000 to 2019 were segregated. Selected articles comprised original research, meta-analysis, and systematic reviews.Results Parameters such as duration, posture, and non-nutritive sucking habits had an impact on effective breastfeeding.Discussion Effective breastfeeding and maintaining appropriate posture and duration helps to positively impact the normal growth and development of the jaws, muscular functioning, and speech. Thereby, the risk of developing malocclusion in primary dentition can be prevented.Conclusion An understanding of the role of breastfeeding and malocclusion will help in the early intervention and prevention of malocclusion and deviated muscular function. Highlighting the role of counseling and effective feeding practices is also an area that should be focused upon by budding clinicians.
Keywords: breastfeeding; bottle feeding; ineffective breastfeeding; malocclusion; pacifier